Protocol for a Cluster Randomised Controlled Trial to Compare the Taste & See Programme - A Church-Based Programme to Develop a Healthy Relationship with Food - With a Wait-List Control - Lycett, Deborah (Religions, 2018)
(1) Background: Obesity is strongly associated with poor mental-health. Spiritual and religious wellbeing is associated with improved mental well-being and reduced emotional eating. Taste & See, a church based programme to help develop a healthy relationship with food has been successfully tested for feasibility in the UK but an adequately powered randomised controlled trial is needed to test efficacy. This paper reports on the protocol for such a trial; (2) Method: A cluster, randomised controlled trial where Christian churches (any denomination) are the unit of randomisation. 150 overweight adults will be recruited from approximately 15 churches (clusters) in the UK, each church (cluster) will recruit approximately 10 participants. Churches will be randomised 2:1 to either begin the Taste & See programme immediately or in 10 weeks' time. Data on eating habits, mental and spiritual health will be collected online before and after the intervention and control period and follow-up will continue until 2 years; (3) Implication of Results: Should the programme prove effective it will provide strong clinical evidence of the role of churches in improving the health and well-being of those struggling with food and weight issues.